Trypanosoma spp in rats (Rattus rattus and Rattus norvegicus) from two environments: food markets and pig farms - Carhuallanqui P., Andrea (2017)
The aim of the study was to determine the presence of Trypanosoma spp in Rattus spp from food markets and pig farms in Lima, Peru, to identify the species of Trypanosoma spp by morphological and biometric characterization, and to correlate the presence of the parasite with the variables sex, age (juvenile and adult), origin and species. The study was conducted in eight food markets of six districts (n = 62 rats) and three pig farms (n = 99) from three districts of Lima. Blood samples were collected and analysed using the thin blood smear technique and stained with «Hemacolor» to determine the presence of the parasite. The identification of the Trypanosome species was based on international keys based on the morphological and biometric characteristics of the trypomastigotes present in blood smears stained with Giemsa. T. lewisi was the only species found in a frequency of 22.5 and 21.2% in rats from the food markets and pig farms, respectively. The frequency of T. lewisi in R. norvegicus and R. rattus was 10.2 and 26.7%, in male and female rats was 21.1 and 22.0%, and in adults and juveniles was 17.0 and 26.5%, respectively. There was no significant association with the variables of origin, sex, and age. R. rattus showed a significant risk factor (OR: 3.77) against R. norvegicus for the presentation of T. lewisi.